Relationship between physiological indices and aerobic performance tests in short and medium term of elite cyclists - Sangali, E. B.; Zapaterra Campos, E.; Agostini Gobbo, L.; de Andrade, V. L.; Papoti, M.; Forte Freitas Junior, I.; Rezende Figueira, T.; Balikian Junior, P. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
Few studies allow usto verify which physiological responses are associated with performance in anational elite cycling group. Therefore, this study aimed to determine and correlate various physiological and aerobic indices with performance in 4 and 20 km time trials in high-level cyclists. The sample consisted of 14 male professional cyclists of the national elite group (28.5 ± 4.7 years old, 73.47 ± 8.29 kg, 176 ± 6.76cm), who performed a progressive test in laboratory to determine maximal oxygen consumption (VO2max: 62.23 ± 8.28 ml•kg-1•min-1), intensity relative to VO2max (iVO2max: 500.83 ± 58.65w), movement economy (EM: 0.1166 ± 0.0362 ml•kg•min•w-1), and the first and second ventilatory threshold (LV1: 348.21 ±43.26 w; LV2: 417.86 ± 60.79 w, respectively). They also performed two time trial performance tests of 4 and 20km. For the correlation between physiological indices and trial performance, Pearson correlation coefficient (p< 0.05) was used. No correlation was found between the physiological indices (VO2max absolute and relative, iVO2max, EM, LV1 and LV2) and performance in 4 km (r= 0.38; 0.16; -0.33; 0.20; -0.50; -0.20, respectively) and 20 km (r= 0.24; 0.01; -0.13; -0.12; -0.48; -0.19, respectively) time trialin high level athletes. These results suggest that these variables are not able to explain the performance in time trials in the respective lengths, probably due to the subjects` homogeneity.